1993
DOI: 10.1007/bf00304325
|View full text |Cite
|
Sign up to set email alerts
|

Function tests on the neuroendocrine hypothalamo-pituitary system following acute midbrain syndrome, with special reference to computertomographical and magnetic resonance imaging results

Abstract: Seventeen patients underwent a neuroendocrinological function test at a mean 6.3 years following a severe craniocerebral trauma (CCT) accompanied by midbrain syndrome. An insulin hypoglycaemia test (IHT) and the combined pituitary anterior lobe test (CPALT) were applied. Whereas the IHT as maximum stimulator of the hypothalamo-pituitary system (HPS) showed an adequate reserve capacity, the CPALT yielded a partial limitation of the secretion dynamic in the somatotropic, adrenocorticotropic axis as well as a dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Thus, 30% to 80% of TBI victims have been found to develop pituitary hormone deficiencies in a variety of combinations (1)(2)(3)(4)(5)(6). So far, gonadal (7)(8)(9) and thyroid axes (10 -13) functions along with adequacy of growth hormone secretion (11)(12)(13)(14) have been extensively investigated.…”
mentioning
confidence: 99%
“…Thus, 30% to 80% of TBI victims have been found to develop pituitary hormone deficiencies in a variety of combinations (1)(2)(3)(4)(5)(6). So far, gonadal (7)(8)(9) and thyroid axes (10 -13) functions along with adequacy of growth hormone secretion (11)(12)(13)(14) have been extensively investigated.…”
mentioning
confidence: 99%
“…We were not able to stimulate the anterior pituitary lobe with releasing hormones. In a study by Lenzen, 22 who investigated the endocrine sequelae of a severe head injury, the stimulated values of cortisol, growth hormone, follicle‐stimulating hormone and prolactin were reduced. The pituitary‐thyroid‐axis, however, was not disturbed.…”
Section: Discussionmentioning
confidence: 99%
“…normal values of hormones were not validated in the intensive care unit (ICU) setting, which makes the interpretation of basal hormones even more difficult. Lenzen et al (1993) reported decreased GH and cortisol responses to GHRH and CRH, respectively, in 17 patients with severe head injury compared to healthy controls but no impairment of GH and cortisol in the insulintolerance test (ITT). Kelly et al (2000) studied pituitary function in 22 patients with moderate to severe head injury and a matched control group.…”
Section: Acute Changes In Pituitary Function After Tbimentioning
confidence: 97%